KAJIAN KOMPARATIF ONTOLOGI VAISESIKA DARSANA DAN KITAB PANATURAN HINDU KAHARINGAN - Arya Maulana Pratama; Eka; Pela Marselina (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
Vaisesika Darsana of Hindu philosophy is one of the Sad Darsanas. It imparts knowledge about the nature of reality, the elements that make up the world, and the law and order in the cosmos. The Holy Panaturan Scriptures of Hindu Kaharingan have teachings about the creation of the universe, the relationship between humans and God, ethical values, and life equality. Both view the order of the universe similarly and believe that God is the primary cause of all things. The purpose of this study is to examine the relationship between Vaisesika Darsana and cosmology and ethical teachings in Panaturan and its relevance for reconstructing the spiritual values ​​of the Hindu Kaharingan community. The method used is a literature study method with a descriptive qualitative approach through analysis of the Vaisesika Darsana text, the Panaturan Book, and other sources, then compared conceptually and thematically. The research showed the relevant concepts of Padartha in Vaisesika Darsana and cosmological doctrine of regulation of the creation, which categorically asserts God (Isvar/Ranying Hatalla Langit) as creator-regulator of nature, as well as equalized a polemic for creating balance among man, nature, and God. The conclusion of this study is, Vaisesika Darsana philosophy has correlation concept with Panaturan teaching in cosmology and ethics aspects that reflect the continuity of classical Hindu values ​​to the Panaturan Hindu Kaharingan teaching in basic life religious harmonious ethics.